2022
DOI: 10.1111/cpr.13216
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor 2 mRNA‐binding protein 2‐regulated alternative splicing of nuclear factor 1 C‐type causes excessive granulosa cell proliferation in polycystic ovary syndrome

Abstract: Objectives Polycystic ovary syndrome (PCOS) is a common reproductive endocrine disorder. Insulin‐like growth factor 2 mRNA‐binding protein 2 (IGF2BP2) serves as an HMGA2 target gene to promote the proliferation of granulosa cells (GCs). However, it is still unclear whether IGF2BP2 participates in the pathogenesis of PCOS as RNA binding protein (RBP). In this study, we aimed to elucidate IGF2BP2‐interacting transcripts, global transcriptome together with alternative splicing in GCs to eventually un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Thus, we hypothesized that insulin might also affect other members of the IGFBP family, such as IGF2BP2 and IGF2BP3, thereby influencing IGF levels. In PCOS patients, IGF2BP2 overexpression is associated with excessive proliferation of the GCs because it preferentially binds to mRNAs with AU‐rich elements (AREs) [13]. This is important because the induction of programmed cell death, called apoptosis, is responsible for the growth of GCs, therefore contributing to the etiology of PCOS [77].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we hypothesized that insulin might also affect other members of the IGFBP family, such as IGF2BP2 and IGF2BP3, thereby influencing IGF levels. In PCOS patients, IGF2BP2 overexpression is associated with excessive proliferation of the GCs because it preferentially binds to mRNAs with AU‐rich elements (AREs) [13]. This is important because the induction of programmed cell death, called apoptosis, is responsible for the growth of GCs, therefore contributing to the etiology of PCOS [77].…”
Section: Discussionmentioning
confidence: 99%
“…Known as insulin-like growth factor II (IGF-II) mRNA-binding protein 2 (IGF2BP2), it binds to the crucial growth and insulin signaling molecule IGF-II. IGF2BP2 is encoded by the IGF2BP2 gene located on chromosome 3q27 [12,13]. PCOS is characterized by insulin resistance; therefore, SNPs linked to the insulin signaling pathways may contribute to the development of PCOS's clinical features [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most notably, ZIKV infection decreased IGF2BP2 interaction with 15 proteins of the mRNA splicing machinery. Interestingly, there is evidence that IGF2BP2 regulates mRNA splicing (38) in addition to its most characterized functions in mRNA stability and translation. Furthermore, several studies reported that ZIKV infection alters mRNA splicing (59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Figure S12). Some of these RBPs are known to regulate splicing, e.g., Rbm4b [44] at 6-week, Son [45] at 11/20-week, and Igf2bp2 [46] at 6/20-week.…”
Section: Deg and Dse Linked To Divergent Biological Processesmentioning
confidence: 99%